2020
DOI: 10.1002/ceat.202000063
|View full text |Cite
|
Sign up to set email alerts
|

Atomization and Mixing Characteristics of Swirl‐Flow Atomizers in the Refining Industry

Abstract: Swirl atomizers are commonly used by refining and chemical companies to wash out ammonium chloride deposits. Experiments and numerical simulation were performed to investigate the atomization and mixing characteristics of swirl atomizers. The volume‐of‐fluid Lagrangian method was applied in the simulation, and its results were compared with experimental data to validate its accuracy. Results demonstrated that the entrainment effect of the airflow changed the atomization angle and coverage area of water. Moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For spherical particles, when the Reynolds number is within a certain range, adopts the following expression [ 17 ]: where C D is the drag coefficient.…”
Section: Simulation Scheme Of Flavoring Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For spherical particles, when the Reynolds number is within a certain range, adopts the following expression [ 17 ]: where C D is the drag coefficient.…”
Section: Simulation Scheme Of Flavoring Equipmentmentioning
confidence: 99%
“…Therefore, some scholars have adopted numerical evaluation to analyze atomization characteristics. For example, Jin et al [ 17 ] studied the liquid film-breaking process and atomization characteristics of swirl atomizers with numerical simulations. The results showed that increases in the gas flow directly affected the mixing characteristics.…”
Section: Introductionmentioning
confidence: 99%